Exploring the Use of Discussion Strategies and Labels in Asynchronous Online Discussion - Gao, Fei (Online Learning, 2014)
Drawing on research in both constrained online discussion environments and strategy instruction, this approach combines explicit instruction on discussion strategies with the use of post type labels. In a trial of this approach in an online course, students actively used the discussion strategies and post type labels in their discussion. Analysis of student posts and survey responses suggested that students in the experimental group used discussion strategies more frequently after the intervention as compared to the control group and perceived that this approach positively impacted their discussions. In addition, there is a certain degree of improvement in the quality of discussion measured by Gunawardena, Lowe and Anderson’s (1997) critical analysis model.